MENAKAR LIBERALITAS PEMIKIRAN AL-ṬŪFĪ TENTANG MAṢLAḤAH DALAM HUKUM ISLAM - Syaiful Bahri, (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
This paper attempts to discuss Najmuddīn al-Ṭūfī’s thought on maslahah, as well as see the extent of his liberal idea. In order to unravel this problem, the author conducted a literature review to examine al-Ṭūfī’s work, Risālah fī Ri’āyah al-Maṣlaḥaḥ. This study resulted in two conclusions. First, al-Ṭūfī’s thought on maslahah is quite controversial because it is delivered with provocative words. Al-Ṭūfī states that in case of confl ict between naṣ and masalahah, the precedence is maslahah using Takhṣīs and Tabyīn mechanisms. Second, al-Ṭūfī’s thought can’t be put into the category of liberal thought. Since, although al-Ṭūfī states the permissibility displacing the position of naṣ with maslahah, the process must be carried out with the Takhṣīṣ and Tabyīn mechanisms which are already popular practiced in Islamic Legal thoughts.